Analiza "crimen ambitus" w świetle hiszpańskich "leges municipales/coloniarum" i wcześniejszych regulacji prawnych - Twarowska-Antczak, Emilia (Rome and Iberia : Inspirations and Connections throughout History, 2021)
In this work, I focus on issues concerning the responsibility of city officials for crimen de ambitu in the light of Spanish leges municipales/ coloniarum and earlier legislation. In a system created by the ancient Romans, responsibility was intended to safeguard the interests of municipalities in the event of management irregularities. Therefore, the applicant for the office of duumvir or quaestor was obliged to set a cash security – cautio. One of the key problems of the Roman republic, and later the Roman municipia (also during the principate) was the corruption of voters with the aim of getting them to cast a ballot for a particular candidate. During the principate era, electoral crime was mainly committed outside Rome, which is why I analyse the legal norms contained in Spanish city laws in the context of Republican legislation.